Total Psoas Area Predicts Complications following Radical Cystectomy - Timothy D. Lyon; Nicholas J. Farber; Leo C. Chen; Thomas W. Fuller; Benjamin J. Davies; Jeffrey R. Gingrich; Ronald L. Hrebinko; Jodi K. Maranchie; Jennifer M. Taylor; Tatum V. Tarin (Advances in Urology)
Purpose. To determine whether total psoas area (TPA), a simple estimate of muscle mass, is associated with complications after radical cystectomy. Materials and Methods. Patients who underwent radical cystectomy at our institution from 2011 to 2012 were retrospectively identified. Total psoas area was measured on preoperative CT scans and normalized for patient height. Multivariable logistic regression was used to determine whether TPA was a predictor of 90-day postoperative complications. Overall survival was compared between TPA quartiles. Results. 135 patients were identified for analysis. Median follow-up was 24 months (IQR: 6–37 months). Overall 90-day complication rate was 56% (75/135). TPA was significantly lower for patients who experienced any complication (7.8 cm2/m2 versus 8.8 cm2/m2, P=0.023) and an infectious complication (7.0 cm2/m2 versus 8.7 cm2/m2, P=0.032) than those who did not. On multivariable analysis, TPA (adjusted OR 0.70 (95% CI 0.56–0.89), P=0.003) and Charlson comorbidity index (adjusted OR 1.34 (95% CI 1.01–1.79), P=0.045) were independently associated with 90-day complications. TPA was not a predictor of overall survival. Conclusions. Low TPA is associated with infectious complications and is an independent predictor of experiencing a postoperative complication following radical cystectomy.